2019
DOI: 10.1002/lary.28142
|View full text |Cite
|
Sign up to set email alerts
|

Elevated exosomal lysyl oxidase like 2 is a potential biomarker for head and neck squamous cell carcinoma

Abstract: Objectives: The secretory enzyme lysyl oxidase like 2 (LOXL2) is speculated to contribute to tumor progression through its functions in the remodeling of extracellular matrix and epithelial-mesenchymal transition. We previously identified elevated expression of LOXL2 in metastatic human head and neck squamous cell carcinoma (HNSCC) cells in a mouse lymph node metastases model. Here we performed a case series study examining LOXL2 expression levels in human serum from HNSCC patients to evaluate whether LOXL2 is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 58 publications
0
11
0
Order By: Relevance
“…They isolated exosomes and found different miRNA loading patterns similar to the loading patterns of blood exosomes, suggesting that circulating exosomes can be a more reliable method in evaluating tumors ( Rabinowits et al, 2017 ). Sanada et al (2020) examined the expression levels of secreted lysyl-oxidase-like 2 (LOXL2) in pharyngeal and tongue cancer patient serum and found that elevated serum exosomes LOXL2 levels are associated with low-grade oral cancer. All these discoveries of exosomes provide new ideas for the non-invasive disease diagnosis method.…”
Section: Survey Methodologymentioning
confidence: 99%
“…They isolated exosomes and found different miRNA loading patterns similar to the loading patterns of blood exosomes, suggesting that circulating exosomes can be a more reliable method in evaluating tumors ( Rabinowits et al, 2017 ). Sanada et al (2020) examined the expression levels of secreted lysyl-oxidase-like 2 (LOXL2) in pharyngeal and tongue cancer patient serum and found that elevated serum exosomes LOXL2 levels are associated with low-grade oral cancer. All these discoveries of exosomes provide new ideas for the non-invasive disease diagnosis method.…”
Section: Survey Methodologymentioning
confidence: 99%
“…Immunoblot analyses revealed that LOXL2 was present in the serum exosomal fractions from three HNSCC patients, and Sanada et al observed approximately threefold higher levels of LOXL2 in the HNSCC patients compared with three healthy volunteers. The hypoxic microenvironment may stimulate tumour cells to generate miRNA-21-rich EXOs that are delivered to normal cells to promote premetastatic behaviours [70]. Similarly, bioinformatics analysis has shown that miR-21-enriched EVs are associated with increased HNSCC metastasis and poor survival [71].…”
Section: Tde Promote Metastasismentioning
confidence: 99%
“…In addition, previous studies had verified that LOXL2 mRNA expression was up-regulated in metastatic HNSCC cells compared with non-metastatic cells ( Demory Beckler et al, 2013 ). Taken together, these results suggest that serum exosome LOXL2 levels are only associated with early-stage HNSCC, and may serve as biomarkers for early diagnosis and a potential target for therapeutic intervention ( Cox et al, 2016 ; Sanada et al, 2020 ). Both protein and mRNA levels of Annexin A1 (ANXA1) were down-regulated in HNSCC.…”
Section: Proteinmentioning
confidence: 76%